ENVIRONMENTAL IMPACTS OF LAND USE CHANGE IN INDUSTRIAL AREAS - Martono, Dwi Nowo; Aruminingsih, Aruminingsih (Journal of Environmental Science and Sustainable Development, 2025)
Industrial development in Indonesia has been predominantly concentrated on Java Island, particularly in Karawang Regency, West Java Province. Covering an area of 175,327 hectares, Karawang has been identified as a strategic region for national food security. The Minister of Agrarian Affairs and Spatial Planning designated 95,667.45 hectares of rice fields as protected agricultural land. However, the expansion of industrial and residential areas within the regency poses a significant threat to its role as the national rice granary and to broader food security. As industrial land occupancy increases, the environmental capacity to support rice production and ensure national food security declines. This study aims to assess the environmental impacts of land use changes in the industrial zones of Karawang Regency for 30 years. Spatial imagery data were processed using supervised classification techniques to Landsat 5 and Landsat 8 TM level 1 geocoded imagery. The environmental impacts were analyzed using Geographic Information Systems (GIS) and further supported by in-depth interviews concerning flood events that occurred over the past five years. The multiple regression analysis was conducted to evaluate the influence of environmental, economic, and social factors on flood impact losses. The results indicated that 55.6% of the variation in flood impact losses could be explained by the combined effect of the three independent variables. The findings revealed substantial land use changes over the past 40 years, with approximately 38,571 hectares (22%) of vegetation and water bodies were lost and replaced by industrial and residential developments, which increased by 31,558 hectares (18%). A strong correlation was observed between land use changes and the environmental impacts of flooding in Karawang Regency. Accordingly, it is recommended that local government implement measure to regulate land conversion to mitigate further environmental degradation. An integrated spatial planning approach that incorporates ecological considerations, is strongly advised to reduce the risk of flooding in industrial areas